AUGMENTED REALITY MEDIA FOR LEARNING ELECTRICAL CIRCUITS: ENHANCING SCIENCE PROCESS SKILLS AND STUDENTS’ ACHIEVEMENT - Nendi Niati; Rahayu Condro Murti; Woro Sri Hastuti (Jurnal Eduscience)
Purpose—The study aims to develop Android-based augmented reality (AR) instructional media for teaching electrical circuits, enhancing students' science process skills and learning outcomes. In addition, this technology can help students develop the science process skills needed in science learning.